Revision of the genus Spinonychiurus Weiner 1996 (Collembola: Onychiuridae) with description of five new species - Pomorski, Romuald J.; Kapruś, Igor J. (Zootaxa, 2015)
The genus Spinonychiurus Weiner, 1996 is revised. This genus is assigned to the tribe Thalassaphorurini because of the structure of reduced furca––a small depression in the center of abdominal sternum IV, with 2+2 small posterior chaetae arranged in two rows. Spinonychiurus clearly differs from other members of the tribe by the division of abdominal sternum III on two subsegments, each with an own set of chaetae. Five new species, S. issykkulensis sp. nov., S. nazguli sp. nov., S. natashae sp. nov., S. alaskensis sp. nov. and S. alabelensis sp. nov. are described. Five previously known species, S. edinensis (Bagnall, 1935), S. spinularius (Gisin, 1952) comb. nov., S. subedinensis (Arbea & Jordana, 1985) comb. nov., S. tianshanicus (Martynova, 1971) comb. nov. and S. pamirensis (Martynova, 1975) comb. nov., are assigned to this genus and redescribed on the basis of the type material and new specimens. An identification key to all known Spinonychiurus species is provided.